2023
DOI: 10.1027/2151-2604/a000527
|View full text |Cite
|
Sign up to set email alerts
|

How Did COVID-19 Affect Education and What Can Be Learned Moving Forward?

Abstract: The COVID-19 pandemic drastically impacted the educational sector on a global front. A plethora of research has been conducted to better understand the effects that the pandemic had on education as a whole, including investigations into different topics (e.g., school closures, e-teaching and learning, mental and physical health), populations (e.g., students, teachers), and levels of education (e.g., school, higher education). To summarize the available literature on education during the pandemic both qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…Within this context, Daumiller et al (2021) observed substantial interindividual differences between faculty members that were partly attributable to between-person motivational differences, underscoring the importance of considering not only contextual, but also individual factors related to university instructors' well-being which have received considerably less empirical attention to date (Watt & Richardson, 2020). Exceptions include studies linking demographic factors such as gender (Blix et al, 1994;Watts & Robertson, 2014) and achievement goals (Daumiller & Dresel, 2020Rinas et al, 2022;Rinas et al, 2023) with subjective well-being in university teaching staff. Individual differences in selfregulating and coping with teaching-related stress are not yet well understood for this population.…”
Section: Subjective Well-being In University Teaching Staffmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, Daumiller et al (2021) observed substantial interindividual differences between faculty members that were partly attributable to between-person motivational differences, underscoring the importance of considering not only contextual, but also individual factors related to university instructors' well-being which have received considerably less empirical attention to date (Watt & Richardson, 2020). Exceptions include studies linking demographic factors such as gender (Blix et al, 1994;Watts & Robertson, 2014) and achievement goals (Daumiller & Dresel, 2020Rinas et al, 2022;Rinas et al, 2023) with subjective well-being in university teaching staff. Individual differences in selfregulating and coping with teaching-related stress are not yet well understood for this population.…”
Section: Subjective Well-being In University Teaching Staffmentioning
confidence: 99%
“…Focal variables were assessed in a contextualized manner, that is, with respect to teaching experiences during the COVID-19-induced lockdown over the course of one semester (T1: November 2020; T2: February 2021), providing a context that likely made teachingrelated stress and coping highly salient and thus ideal grounds for analyzing reciprocal relations between coping and well-being. We followed prior research in conceptualizing both coping (task-oriented; emotionoriented; avoidance-oriented) and well-being (positive affect; negative affect; job satisfaction) as multidimensional constructs (Endler & Parker, 1990;Rinas et al, 2023). Based on our review of prior research and theorizing above, we generally expected T1 well-being to predict changes in coping strategy use at T2.…”
Section: Overview Of the Present Study: Aims And Hypothesesmentioning
confidence: 99%
“…The unprecedented crisis caused by the COVID-19 pandemic has affected all socioeconomic areas and has escalated into a humanitarian crisis that threatened millions of people worldwide. The field of higher education (HE) has not been an exception, as university students have been heavily impacted by the adverse effects of the pandemic [1].…”
Section: Introductionmentioning
confidence: 99%